377 OUTCOME OF COMBINED KIDNEY AND REDO HEART TRANSPLANT RECIPIENTS FROM A SINGLE CENTER. Issue 1 (1st January 2007) - Chinakarn, L.; Kawano, M. A.; Song, H.; Patel, J. K.; Hamilton, M. A.; Kobashigawa, J. A.
Abstract : Purpose: Outcomes of patients with combined heart and kidney transplantation have been comparable to those of heart transplant patients alone. As heart transplant patients develop severe graft failure (usually due to an accelerated form of atherosclerosis in the coronary arteries of the donor heart), the need for a second heart transplant becomes necessary. These patients may also have developed severe renal dysfunction due to chronic calcineurin inhibitor use. The outcome of patients with redo heart transplant combined with kidney transplant has not been established. In our single-center experience we examined the outcome of simultaneous kidney and redo heart transplantation. Methods: Between 1992 and 2006, we reviewed 557 heart transplant surgeries with five combined kidney and redo heart transplant surgeries. Outcomes, including first-year rejections and survival, were recorded. All patients were treated with triple-drug therapy including cyclosporine ( n = 342) or tacrolimus ( n = 215) in combination with azathioprine ( n = 269) or mycophenolate mofetil ( n = 257) or sirolimus ( n = 12) plus or minus corticosteroids. Results: There were five patients with combined kidney and redo heart transplants, four were male, with the average age of 49, and cause for renal transplant included cyclosporine nephrotoxicity, chronic nephroschierosis, etc. Combined kidney and redo heart transplant patients had comparable first-year rejection episodes (20% vs 32%) and comparable first-year survival (80% vs 94%) compared with heart transplant alone. Conclusions: Combined kidney and redo heart transplantation has comparable first-year rejection and survival. Therefore, the addition of simultaneous kidney transplant to redo heart transplant surgery does not confer short-term added risk.